1998
DOI: 10.1002/(sici)1097-0142(19980715)83:2<245::aid-cncr7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

18F-labeled fluorouracil positron emission tomography and the prognoses of colorectal carcinoma patients with metastases to the liver treated with 5-fluorouracil

Abstract: BACKGROUND Although many factors have been investigated in connection with the prognoses of colorectal carcinoma patients with metastases to the liver, a means for evaluating response and prognosis prior to the administration of standard chemotherapy has not been available. Positron emission tomography (PET) is a noninvasive means of measuring the distribution of radiolabeled cytostatic agents in tumor regions. METHODS Prior to the administration of 5‐fluorouracil chemotherapy, the authors examined 14 colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The process of integrating dynamic PET assessment into early-phase clinical trials to obtain information on drug distribution to normal and tumor tissues has been applied in the development of a number of anticancer drugs such as 5-FU, BCNU (an alkylating agent specific for brain tissue), DACA (a topoisomerase I/II inhibitor), and SMT487 (a somatostatin analogue). [20][21][22][23] However, the major barriers to the utility of dynamic PET for plasma and tissue PK evaluation are the short follow-up time of PET and its inability to distinguish the radiolabeled parent drug and metabolites. This study, for the first time to our best knowledge, presents a pharmacometric modeling approach to overcome these barriers by simultaneously modeling dynamic PET tissue data and long-term conventional plasma PK data.…”
Section: Discussionmentioning
confidence: 99%
“…The process of integrating dynamic PET assessment into early-phase clinical trials to obtain information on drug distribution to normal and tumor tissues has been applied in the development of a number of anticancer drugs such as 5-FU, BCNU (an alkylating agent specific for brain tissue), DACA (a topoisomerase I/II inhibitor), and SMT487 (a somatostatin analogue). [20][21][22][23] However, the major barriers to the utility of dynamic PET for plasma and tissue PK evaluation are the short follow-up time of PET and its inability to distinguish the radiolabeled parent drug and metabolites. This study, for the first time to our best knowledge, presents a pharmacometric modeling approach to overcome these barriers by simultaneously modeling dynamic PET tissue data and long-term conventional plasma PK data.…”
Section: Discussionmentioning
confidence: 99%
“…Total bilirubin >1. 5 Open access ► Inability to lie in prone position. ► A medical or psychiatric condition or other circumstances which would significantly decrease the chances of understanding the informed consent process, obtaining reliable data, achieving study objectives or completing the study treatment and/or examinations.…”
Section: Exclusion Criteriamentioning
confidence: 99%
“…5-fluorouracil and docetaxel. Higher tumour uptake of radio-active labelled 5-fluorouracil or docetaxel chemotherapy on positron emission tomography (PET) was shown to correlate, respectively, with longer survival in patients with liver metastasis of colorectal carcinoma 5 and with better tumour response in lung cancer patients. 6 In a study comparing different dose schedules of the adjuvant AC regimen, the highest dosages (60 mg/m 2 doxorubicin and 600 mg/m 2 cyclophosphamide) were most effective, and this is currently the standard of care.…”
Section: Introductionmentioning
confidence: 99%
“…As tumor response to anticancer drugs is thought to be directly related to drug concentrations in tumor tissue, uptake of radiolabeled anticancer drugs in tumors may predict treatment outcome. Preliminary PET studies using F-18 labeled 5-fluorouracil ([ 18 F]5-FU; (9, 10)), tamoxifen ([ 18 F]fluorotamoxifen; (11)), and C-11 labeled docetaxel ([ 11 C]docetaxel; (12)) showed that high tumor uptake of the radiolabeled anticancer drug was associated with improved tumor response following corresponding therapy. These studies suggest that radiolabeled anticancer drugs may be useful for prediction of outcome prior to start of treatment.…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…These studies suggest that radiolabeled anticancer drugs may be useful for prediction of outcome prior to start of treatment. Consequently, an increasing number of anticancer drugs has now been radiolabeled including radiolabeled cytotoxic agents (e.g., [ 11 C]temozolomide, [ 18 F]5-fluorouracil, and [ 11 C]docetaxel), selective hormone receptor modulators (e.g., [ 18 F]fluorotamoxifen), tyrosine kinase inhibitors (TKIs, e.g., N-[ 11 C]methylimatinib, [ 11 C]sorafenib, and [ 11 C]erlotinib), and monoclonal antibodies [Mabs, e.g., [ 89 Zr]cetuximab, [ 89 Zr]trastuzumab, and [ 89 Zr]bevacizumab; (10, 11, 1320)].…”
Section: Positron Emission Tomographymentioning
confidence: 99%